Curator Searching for Urban Identity; From ''Yousef Abad'' to ''Vali Asr'' - Nezhad, Roudabeh Tankarami Bagheri (European Journal of Sustainable Development, 2020)
By changing the approach of modern art from the middle of the twentieth century to attention to conceptual art, art exhibitions became a spiritual movement that could provide different ways of shaping society. At the same time, the Curator becomes mediator between art and its audience. Victoria D Alexander considers the quality and impact of art on audiences in today's world dependent on distribution systems by presenting a "Better Culture Diamond" based on Wendy Griswold's Crystal Diamond Design. In this analytic-descriptive study, its data were collected through library studies, field research and interviews, while highlighting the importance of Curator as an important part in the art distribution system by examining two Curatorial projects names "Vali Asr-First Folder" and "Yousef Abad" have come to the conclusion that contemporary Curator in Iran represent the social role of art and seek to redefine social concepts such as "urban identity" through Curatorial projects. Keywords: Curator, Contemporary Iranian Art, Cultural Diamond, Urban Identity, Identity Crisis